2010
DOI: 10.1088/0953-4075/43/22/225202
|View full text |Cite
|
Sign up to set email alerts
|

Cross sections for electron scattering by ethane in the low- and intermediate-energy ranges

Abstract: We present a joint theoretical-experimental study on electron scattering by ethane (C 2 H 6 ) in the low-and intermediate-energy ranges. Calculated elastic differential, integral and momentum transfer as well as total (elastic + inelastic) and total absorption cross sections are reported for impact energies ranging from 1 to 500 eV. Also, experimental absolute elastic cross sections are reported in the 40-500 eV energy range. A complex optical potential is used to represent the electron-molecule interaction dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 52 publications
3
28
0
Order By: Relevance
“…We also observe that the SEP values from pentanol follow those of pentane, except that the permanent dipole of pentanol produces a somewhat more pronounced forward peak at E 0 = 5 and 10 eV. Above the ionization potential, this is [46]; Mapstone and Newell [47], × Curry and Newell [48], Merz and Linder [49], ♦ Rawat et al [9], and Fink et al [50]. Propane: Boesten et al [10] and Souza et al [12].…”
Section: A Pentanementioning
confidence: 55%
See 1 more Smart Citation
“…We also observe that the SEP values from pentanol follow those of pentane, except that the permanent dipole of pentanol produces a somewhat more pronounced forward peak at E 0 = 5 and 10 eV. Above the ionization potential, this is [46]; Mapstone and Newell [47], × Curry and Newell [48], Merz and Linder [49], ♦ Rawat et al [9], and Fink et al [50]. Propane: Boesten et al [10] and Souza et al [12].…”
Section: A Pentanementioning
confidence: 55%
“…Ignition and reaction chemistry involving excitation, dissociation, and ionization of these molecules in combustion (plasma) processes in automobile engines [3] is governed or catalyzed by energetic electron scattering from these fuel species in the energy region which ranges from 0.1 eV to high energies (>100 eV), but with a maximum around 10 eV [4]. Whereas there exist electron impact data on methane [5][6][7], ethane [8,9], propane [10][11][12], and butane [13], and in references cited within these, there is lack of electron collision data for pentane. The few data available for pentane are those by Freeman et al [14] of total electron cross sections determined from the mobility of electrons in liquid pentane at the energies of 0.1 to 0.5 eV using a time-of-flight method and those by Kimura et al [15] of gaseous pentane of total cross sections for this target.…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, a modified version of the quasifree scattering model (QFSM) of Staszewska et al [50], known as the scaled quasifree scattering model (SQFSM) [49,51], is used to account for the absorption effects. The SQFSM has already been successfully applied to investigate electron collisions on several targets [49,[51][52][53][54][55]. Also recently, in a benchmark study Staszewska et al [56] confirmed the effectiveness of the SQFSM in describing electron-atom scattering.…”
Section: Theory and Calculationmentioning
confidence: 96%
“…In the recent past, this method was successfully applied by our group to treat electron collisions with ethane, propane, and pyrimidine [20][21][22]. In this work, we extend its application to DME.…”
Section: Theory and Numerical Proceduresmentioning
confidence: 99%